2018
DOI: 10.3126/bjhs.v3i2.20934
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amylase in Patients of Chronic Kidney Disease Stage Three to Stage Five

Abstract: Introduction: Chronic Kidney Disease (CKD) is a progressive loss in renal function over period of many months or years. As compared to the past decades, the number of kidney diseases leading to end CKD is increasing in Nepal. The disease is associated with the decreased glomerular filtration rate (GFR). There is decline in nephron function and number generally quantitated as reduction in glomerular filtration rate. As the GFR declines, there is accumulation of metabolic end products excreted by Kidney. Chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…( 21) A similar study conducted by Pal A used the same formula for calculating GFR and his study was conducted in Nepal. (22) One noteworthy nding in our study is that a huge proportion of patients, 184 out of 196, had concurrent hypertension while in other studies diabetes was seen more frequently in patients with CKD as compared to hypertension. (3,4,23,24) Studies have shown a rise in pancreatic enzymes in serum with the progression of CKD.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…( 21) A similar study conducted by Pal A used the same formula for calculating GFR and his study was conducted in Nepal. (22) One noteworthy nding in our study is that a huge proportion of patients, 184 out of 196, had concurrent hypertension while in other studies diabetes was seen more frequently in patients with CKD as compared to hypertension. (3,4,23,24) Studies have shown a rise in pancreatic enzymes in serum with the progression of CKD.…”
Section: Discussionmentioning
confidence: 44%
“…A study also showed that this elevation is also in uenced by stage of CKD. (22) This means that there must be different reference ranges for amylase for each stage of CKD to eliminate the false positives. Serum amylase can be misinterpreted and give false positives if used in CKD as a marker for pancreatic damage.…”
Section: Discussionmentioning
confidence: 99%
“…Open Access 2023, (17), ( 1 ):72-84 is recommended. The findings of this study provide important insights into the impact of dialysis membranes during multiple sessions on various liver enzymes and pancreatic function in patients with endstage renal disease (ESRD) [39].…”
Section: Journal Of University Of Anbar For Pure Science (Juaps)mentioning
confidence: 99%